Development and Evaluation of a Fidelity Instrument for PEARLS - Farren, Laura; Snowden, Mark; Steinman, Lesley; Monroe-DeVita, Maria (Frontiers in Public Health, 2015)
Purpose This manuscript describes the development and the preliminary evaluation of a fidelity instrument for the Program for Encouraging Active and Rewarding Lives (PEARLS), an evidence-based depression care management (DCM) program. The objective of the study was to find an effective, practical, multidimensional approach to measure fidelity of PEARLS programs to the original, research-driven PEARLS protocol in order to inform program implementation at various settings nationwide. Methods We conducted key informant interviews with PEARLS stakeholders, and held focus groups with former PEARLS clients, to identify core program components. These components were then ranked using a Q-sort process, and incorporated into a brief instrument. We tested the instrument at two time points with PEARLS counselors, other DCM program counselors, and non-DCM program counselors (n = 56) in six states. Known-groups method was used to compare findings from PEARLS programs, other DCM programs, and non-DCM programs. We asked supervisors of the counselors to complete the fidelity instrument on behalf of their counselors to affirm the validity of the results. We examined the association of PEARLS program fidelity with individual client outcomes. Results Program for Encouraging Active and Rewarding Lives providers reported the highest fidelity scores compared to DCM program providers and non-DCM program providers. The sample size was too small to yield significant results on the comparison between counselor experience and fidelity. Scores varied between PEARLS counselors and their supervisors. PEARLS program fidelity was not significantly correlated with client outcomes, suggesting that other implementation factors may have influenced the outcomes and/or that the instrument needs refinement. Conclusion Our findings suggest that providers may be able to use the instrument to assess PEARLS program fidelity in various settings across the country. However, more rigorous research is needed to evaluate instrument effectiveness.